Tropical limestone forest resilience and late Pleistocene foraging during MIS-2 in the Tràng An massif, Vietnam - Rabett, R.; Ludgate, N.; Stimpson, C.; Hill, E.; Hunt, C.; Ceron, J.; Farr, L.; Morley, M.; Reynolds, T.; Zukswert, H.; Simpson, D.; Nyiri, B.; et al. (Pergamon-Elsevier Science Ltd, 2016)
In this paper we present a multi-proxy study of tropical limestone forest and its utilization by human groups during the significant climatic and environmental upheavals of MIS-2 (29-11.7 kBP). Our data are drawn from new field research within the Tràng An World Heritage property on the edge of the Red River Delta, northern Vietnam. Key findings from this study include 1) that limestone forest formations were resilient to the large-scale landscape transformation of the Sunda continent at the end of the last glaciation; 2) that prehistoric human groups were probably present in this habitat through-out MIS-2; and 3) that the forested, insular, karst of Tràng An provided foragers with a stable resource-base in a wider changing landscape during the late Pleistocene and into the Holocene. These results have implications for our understanding of the prehistoric utilization of karst environments, and resonance for their conservation in the face of climate and environmental change today.